2013
DOI: 10.4310/hha.2013.v15.n2.a7
|View full text |Cite
|
Sign up to set email alerts
|

Effective descent morphisms in star-regular categories

Abstract: In this article a sufficient condition on a star-regular category is introduced guaranteeing that regular epimorphisms are effective descent morphisms. This condition is satisfied by any category with a good theory of ideals (thus, in particular, by any ideal determined category), by any almost abelian category (for instance, by the categories of torsion abelian groups, torsion-free abelian groups, normed vector spaces, Banach spaces, locally compact abelian groups, etc.) and by any category of topological Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…From the syntactic characterisation of 0-regular varieties obtained in [8], the following property of such varieties can be easily deduced: the congruence generated by the 0-class of a reflexive homomorphic relation always contains the reflexive relation as a subrelation. In [13] it was shown that a similar fact holds more generally in any star-regular category. In this paper we refine and further generalise this result -see Theorem 2.2 below.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…From the syntactic characterisation of 0-regular varieties obtained in [8], the following property of such varieties can be easily deduced: the congruence generated by the 0-class of a reflexive homomorphic relation always contains the reflexive relation as a subrelation. In [13] it was shown that a similar fact holds more generally in any star-regular category. In this paper we refine and further generalise this result -see Theorem 2.2 below.…”
Section: Introductionmentioning
confidence: 71%
“…So, since a regular epimorphism is always a coequalizer of its kernel pair, and since any kernel pair in a regular category has a coequalizer, star-regularity states precisely that kernel pairs satisfy ( * π 0 ). In [13] it was shown that in a star-regular category every reflexive relation satisfies ( * π 0 ). In fact, we have: Theorem 2.2.…”
Section: Internal Reflexive Graphsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, this is the case for any category of topolo-gical Mal'tsev algebras [19], then in particular for the category of topological groups. Also any almost abelian category in the sense of [21] is almost exact (see [12]). Another example of almost exact category is provided by the category of regular epimorphisms in an exact Goursat category [16].…”
Section: Pullback Properties In Regular Gumm Categoriesmentioning
confidence: 99%
“…Therefore Gp(Top) is neither a semi-abelian category nor an almost abelian category. Nevertheless, it is known that every topological semi-abelian variety is (cocomplete and) homological [4, Theorem 50] and descent-exact [29,Section 4.5]. Note that the categories of models of semi-abelian theories in the category of compact Hausdorff spaces are themselves semi-abelian categories [4,Theorem 50].…”
Section: Introductionmentioning
confidence: 99%